Clinical, research, and public health implications of poor measurement of Vitamin D status - Lucas, R.; Gorman, S.; Black, Lucinda; Neale, R. (2017)
There is widespread concern about the high prevalence of Vitamin D deficiency amid evidence to support that such a state may increase the risk of a wide range of adverse health outcomes. Estimating the prevalence of deficiency, as well as establishing links to health outcomes, requires the accurate and precise measurement of 25-hydroxyVitamin D [25(OH)D] in serum or plasma. Accurate measurement of 25(OH)D underlies the definitions of Vitamin D deficiency, insufficiency, and sufficiency and, thus, prevalence estimates. Imprecise measurement of 25(OH)D in epidemiological research can result in incorrect null findings of associations with disease. When associations with disease are found, the inaccuracy of measurement forestalls defining the absolute level of 25(OH)D that is associated with increased risk. For the clinician, both inaccuracy and imprecision are problematic, because clinical care is most often based on a single measurement to define Vitamin D status. New initiatives to develop a standard reference method and the assignment of "true" values to samples provide a solution to these problems. The use of standardized assays in large population studies will allow comparisons to be made between populations and over time that have not previously been possible and will improve our understanding of the role of Vitamin D in health and disease.